Crack monitoring and failure investigation on inkjet printed sandwich structures under quasi-static indentation test - Dikshit, Vishwesh (2018)
In this research contribution, effort is taken to monitor the crack initiation and crack propagation of three-dimensional (3D) printed corrugated sandwich structures using acoustic emission technique. Vertical pillars were introduced in between the existing sinusoidal wave-like corrugations to improve the load bearing capacity of these structures. The vertical pillared corrugated structures were 3D printed with single and multi-material combinations in the facesheet and tested for their indentation resistance. To monitor the exact invisible crack initiation and crack propagation in the 3D printed corrugated structures, a highly-sensitive acoustic emission (AE) testing method was introduced. The resulting AE data points during testing illustrated a cluster of low amplitude data points from 40 to 65 dB indicating invisible crack initiations. High amplitude points up to 95 dB indicated visible cracks propagating until the end of specimen failure. Prevalent failure mechanism for single material (type A) specimens was found to be shear cracking of facesheets with micro steps and failure mechanism of multimaterial (type B) specimens were found to be delamination and shear cracking of multimaterial layers. Load bearing capacity was maximum at 2.14 ± 0.3 kN for type A specimens under a flat indenter with a displacement of 2.12 ± 0.4 mm.